PENGARUH DER DAN INVESTMENT OPPORTUNITY SET TERHADAP NILAI PERUSAHAAN - Wachidah Fauziyanti; Enny Puji Astuti (Sekolah Tinggi Ilmu Ekonomi Semarang, 2018)
This research was performed to analyze the influence of debt equity ratio (DER) and investment opportunity set (IOS) on firm value . Sample of this research was companies listed in Indonesian Stock Exchange (BEI) and include in the LQ 45 index for the period of 2004-2006. Data was collected from annual reports recorded in the 2007 Indonesian Capital Market Directory (ICMD) and was analyzed using regression model. The result of this research showed that DER negatively and IOS positively affected firm values.